Circulating endothelial cells in relapse and limited granulomatous disease due to ANCA associated vasculitis. Issue 2 (8th September 2005) - Woywodt, A; Goldberg, C; Kirsch, T; de Groot, K; Erdbruegger, U; Haller, H; Haubitz, M
Abstract : Objectives: To evaluate numbers of circulating endothelial cells (CECs) in ANCA associated vasculitis and compare vasculitic relapse with limited granulomatous disease. Methods: Sixteen patients with vasculitic relapse of ANCA associated vasculitis and 12 patients with limited granulomatous disease due to Wegener's granulomatosis (WG) were studied. Six patients with newly diagnosed vasculitic disease and six patients with vasculitis with infectious complications were also studied. Twenty two patients in remission were studied, as were 20 healthy controls. Counting of CECs was performed with anti-CD146 driven immunomagnetic isolation and staining with Ulex Europaeus lectin 1(UEA-1). Results: Patients with vasculitic relapse had markedly increased numbers of circulating endothelial cells (12–800 cells/ml, median 88 cells/ml) as did patients with newly diagnosed systemic vasculitis (20–216 cells/ml, median 56 cells/ml). Patients with limited granulomatous disease due to WG had only slightly increased cell numbers (4–44 cells/ml, median 20 cells/ml), which were similar to those of patients in remission (4–36 cells/ml, median 16 cells/ml). Numbers of CECs in patients with granulomatous disease were significantly lower than in those patients with relapse or new onset vasculitis (p<0.001). Cell numbers in patients with relapse and new onset vasculitis declined with immunosuppressive treatment. Patients with infection had 4–36 cells/ml (median 10 cells/ml). A cut off value of 20 cells/ml for a positive result yielded 64% specificity and 95% sensitivity for active systemic vasculitis; the positive predictive value was 63% and the negative predictive value 95%. Conclusion: Markedly increased numbers of CECs discriminate active vasculitis from limited granulomatous disease and remission. These findings add further proof to the concept of CECs as a marker of ANCA associated small vessel vasculitis.